On the taxonomic status of three enigmatic Indochinese frog species (Amphibia: Anura) described by L. G. Andersson - Poyarkov, Nikolay A.; Solovyeva, Evgeniya N.; van Nguyen, Tan; Geissler, Peter (Zootaxa, 2020)
In the first half of the 20th century, four Swedish expeditions to Indochina contributed significantly to the knowledge on the herpetofauna of mainland Southeast Asia. The collected material was examined by L. G. Andersson in Stockholm, resulting in the description of seven new species and forms of amphibians and reptiles from Vietnam and Thailand. However, the taxonomic status of three enigmatic frog species described by Andersson, namely Rana scutigera, Oxyglossus laevis var. vittata, and Microhyla fusca, remained doubtful. All three taxa are only known from their type specimens and their short original descriptions. Though subsequent studies have doubted their validity or systematic assignment, they have been treated as valid species until today. We have examined the external morphology and coloration of the type specimens, what led to a taxonomic reallocation of these three species. We demonstrate that Rana scutigera Andersson, 1916 is a junior synonym of Polypedates megacephalus Hallowell, 1861, Oxyglossus laevis var. vittata Andersson, 1942 is synonymized with Occidozyga martensii (Peters, 1967), and Microhyla fusca Andersson, 1942 represents a junior synonym of Microhyla butleri Boulenger, 1900.